Intra articular distal radius fractures and volar plate fixation: a prospective study - Kundu, Atin Kumar; Wale, Nitin; Phuljhele, Satyendra; Ghritlahre, Deepak; Gurudatta, Harjot Singh (International Journal of Research in Orthopaedics, 2017)
Background: Despite being one of the most common fractures encountered in patients, intra-articular distal radius fractures still pose therapeutic challenge to Orthopaedic surgeons. With the advent of locking plates, the fixation of these fractures has been made better, specifically by fixed angle volar locking plate. This study investigates the efficacy of these plates using volar approach, functional and clinical outcome, in addition to the radiological alignment. Methods: Thirty patients with closed distal radius fractures, with AO TYPE B3, B4, AND C fracture pattern, operated with distal radius plate fixation using volar approach, were included in the study during the period of August 2014 to August 2016. With a minimum follow up of six months, radiological outcome was analysed and functional outcome recorded (Gartland and Werley’s demerit scoring system). Results: With a mean age of 42 years and follow up of six months, the range of movement of the wrist was very satisfactory, and the mean grip strength was 80% of the opposite wrist. Radiological parameters were well‑maintained, and functional parameters by Gartland and Werley showed a significant improvement in most of the patients during the follow‑up period. The complication rate was less and insignificant. Conclusions: Primary volar plate fixation of intraarticular distal radius fracture provides a stable construct that helps in early mobilization, thereby better functional outcomes and minimizes chances of delayed/malunion.